2006
DOI: 10.1016/j.procbio.2006.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Stream microcosm for investigating GEM impact on the indigenous bacterial community in river water and sediment

Abstract: This is a postprint of an article published in Pauling, B.V., Wagner-Döbler, I. Stream microcosm for investigating GEM impact on the indigenous bacterial community in river water and sediment (2006) Process Biochemistry, 41 (10), pp. 2129-2137.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Bacterial ecology, in contrast, has focused on defining and describing the diversity of taxa and classifying them into ecotypes (1,2). However, many studies have shown associations between particular bacterial communities and characteristics of the physical environment they are found in, for instance, soil (3,4) and freshwater (5) habitats, and of the seasonal dynamics of the bacterial community structure (6).…”
mentioning
confidence: 99%
“…Bacterial ecology, in contrast, has focused on defining and describing the diversity of taxa and classifying them into ecotypes (1,2). However, many studies have shown associations between particular bacterial communities and characteristics of the physical environment they are found in, for instance, soil (3,4) and freshwater (5) habitats, and of the seasonal dynamics of the bacterial community structure (6).…”
mentioning
confidence: 99%